2013
DOI: 10.1152/ajpendo.00462.2012
|View full text |Cite
|
Sign up to set email alerts
|

Short-term weight loss attenuates local tissue inflammation and improves insulin sensitivity without affecting adipose inflammation in obese mice

Abstract: Obesity is a major cause of insulin resistance, and weight loss is shown to improve glucose homeostasis. But the underlying mechanism and the role of inflammation remain unclear. Male C57BL/6 mice were fed a high-fat diet (HFD) for 12 wk. After HFD, weight loss was induced by changing to a low-fat diet (LFD) or exercise with continuous HFD. The weight loss effects on energy balance and insulin sensitivity were determined using metabolic cages and hyperinsulinemic euglycemic clamps in awake mice. Diet and exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 34 publications
8
41
1
Order By: Relevance
“…In fact, recent studies indicate that obesity-mediated inflammation and macrophage accumulation develop in multiple organs, including skeletal muscle, liver, pancreas, heart, and brain (9)(10)(11)(12)(13). In that regard, our recent study found that exercise-mediated weight loss improved insulin action without affecting adipose tissue inflammation in mice with diet-induced obesity (7). Additionally, improved insulin action following weight loss was associated with reduced local inflammation in skeletal muscle, suggesting an important role of muscle inflammation in obesity-mediated insulin resistance (7).…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…In fact, recent studies indicate that obesity-mediated inflammation and macrophage accumulation develop in multiple organs, including skeletal muscle, liver, pancreas, heart, and brain (9)(10)(11)(12)(13). In that regard, our recent study found that exercise-mediated weight loss improved insulin action without affecting adipose tissue inflammation in mice with diet-induced obesity (7). Additionally, improved insulin action following weight loss was associated with reduced local inflammation in skeletal muscle, suggesting an important role of muscle inflammation in obesity-mediated insulin resistance (7).…”
mentioning
confidence: 63%
“…In that regard, our recent study found that exercise-mediated weight loss improved insulin action without affecting adipose tissue inflammation in mice with diet-induced obesity (7). Additionally, improved insulin action following weight loss was associated with reduced local inflammation in skeletal muscle, suggesting an important role of muscle inflammation in obesity-mediated insulin resistance (7). These findings clearly contest the adipocentric view of insulin resistance.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…WAT is a source of obesity-induced chronic inflammation [1]; however, it is not the only organ that develops macrophage accumulation in obesity. In fact, recent studies have challenged the causal role of WAT inflammation in obesity-linked metabolic dysregulation of the whole body [2,3]. In addition, it was suggested that local inflammation and ectopic lipid accumulation in skeletal muscle leads to impaired insulin signaling [2].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent studies have challenged the causal role of WAT inflammation in obesity-linked metabolic dysregulation of the whole body [2,3]. In addition, it was suggested that local inflammation and ectopic lipid accumulation in skeletal muscle leads to impaired insulin signaling [2]. Furthermore, inflammation in skeletal muscle and the accumulation of macrophages are observed not only in metabolic diseases but also in certain conditions, such as aged muscle [4], acute muscle damage by high-intensity eccentric exercise [5,6], or chronic diseases (including cancer cachexia) [7], which leads to physical inactivity and aggravates the loss of skeletal muscle oxidative capacity, and vice versa [8].…”
Section: Introductionmentioning
confidence: 99%